2020
DOI: 10.3390/ijerph17041382
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Preterm Birth and Low Birth Weight in Abu Dhabi, the United Arab Emirates

Abstract: Both preterm birth and low birth weight (LBW) represent major public health problems worldwide due to their association with the catastrophic effects of morbidity and mortality. Few data exist about such adverse pregnancy outcomes. The current study aimed to investigate the prevalence of and factors associated with preterm birth and LBW among mothers of children under two years in Abu Dhabi, United Arab Emirates. Data were collected in clinical and non-clinical settings across various geographical areas in Abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
51
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 44 publications
10
51
4
Order By: Relevance
“…In this study, the odds of delivering a LBW baby was signi cantly high among women who delivered their babies through CS compared to those with vaginal deliveries. This nding resonates with a studies conducted in the United Arab Emirates (27) and China (32). Some studies have reported an epidemic of CS which these studies have found to increase adverse birth outcomes such as LBW and preterm delivery (33,34).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In this study, the odds of delivering a LBW baby was signi cantly high among women who delivered their babies through CS compared to those with vaginal deliveries. This nding resonates with a studies conducted in the United Arab Emirates (27) and China (32). Some studies have reported an epidemic of CS which these studies have found to increase adverse birth outcomes such as LBW and preterm delivery (33,34).…”
Section: Discussionsupporting
confidence: 83%
“…The prevalence of LBW in this study is also higher than what was reported in the United Arab Emirates. That study reported a prevalence of 9.4% (27). This could be attributed to geographical differences in study sites.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This is relatively higher than what is reported from other lowincome countries. 31 Of notice, two-thirds of the preterm infants in our cohort were born at late preterm gestation. The increasing rate of late preterm delivery is consistent with other reports.…”
Section: Resultsmentioning
confidence: 81%
“…In a multi-center prospective study conducted by Abdel Razeq et al involving 18 hospitals in Jordan and published in 2017, the rate of prematurity among singleton pregnancies was 5.8% with 85% being delivered after 32-week gestation [ 5 ]. Data from single-center studies showed a prematurity rate of 6.5% in Saudi Arabia, 6% in United Arab Emirates, and 9.7% in Oman [ 6 , 23 ]. The higher rate in our study could be attributed to the fact that our center is the main referral institution in North of Jordan where most high-risk pregnancies, including multiple gestations, are transferred for obstetric care and delivery.…”
Section: Discussionmentioning
confidence: 99%